PEMANFAATAN SAMPAH ORGANIK MENJADI ECO ENZYME SEBAGAI SOLUSI PUPUK RAMAH LINGKUNGAN DI LINGKUNGAN SD WONOSARI 01, KECAMATAN PUGER, KABUPATEN JEMBER - Kusumawati Shindi Nur Rahmawati; Sofyan Sofyan; Kendid Mahmudi (Program Studi Pendidikan IPA FKIP Universitas Jember, 2023)
This study aims to utilize organic waste that has not been considered by the community so far to become a versatile product in the form of eco enzyme in Wonosari Village, Puger District, Jember Regency. This research was conducted in May 2023 using a mixed method of qualitative and quantitative methods using analytic descriptive analysis. Data collection techniques used are interviews, questionnaires, observation, and documentation. The results of this study indicate that the existence of organic waste in the community is still being neglected. There are many ways that can be used to manage organic waste, one of which is by making eco enzymes from organic waste. The training on making eco enzymes in the Elementary School Wonosari 01 area received a positive response. It was found that there was a significant increase in knowledge about organic waste management, from a percentage of 0% to 81.8% in the good category. While the moderate and less categories decreased from 36.4% to 18.2% the moderate category and from 63.6% the less category became 0%.